New type of micro-bipolar plate for micro-fuel cells using LIGA technology together with improved and cost-effective electroplating processes for PCBs. (November 2015) - Baumgärtner, M.; Lanzinger, G.; Hahn, L.; Schulz, J.; Helm, P.; Wartmann, J.
Abstract : A new type of micro-bipolar plate for micro-fuel cells was developed. This micro-bipolar plate was realised using LIGA technology (laser lithography system) together with improved electroplating processes for printed circuit boards (copper, nickel, gold) to produce micro-fuel cells with reduced precious metal loading, increased activity and durability, lower weight and negligible corrosion, and, in addition, lower production cost.